Diversity and Equity in the Distribution of Teachers With Special Education Credentials - North Cooc; Man Yang (SAGE Publishing, 2016)
The shortage of special education teachers (SETs) is a persistent challenge in the United States, but less is known about two other important issues that affect students with disabilities: racial diversity within the SET workforce and the distribution of SETs. Using administrative data on all teachers in California from 1997 to 2014, we examine the racial composition and distribution of teachers with special education credentials. Our results from descriptive and regression analyses show that while teachers with special education credentials remain majority White, the number of teachers of color with special education credentials has increased at a rate more than twice that of general education teachers and special education students of color. We also find that much of the distribution of teachers with special education credentials occurs across districts within the same regional county, while disparities in teacher qualifications are larger by school poverty, racial composition, and student achievement. The results have policy implications for improving diversity and educational equity within the special education workforce.